Impact of Replacing Conventional Complete Dentures with Implant-Supported Fixed Complete Dentures - Compagnoni, Marco Antonio [UNESP]; Paeari, Andre Gustavo [UNESP]; Rodriguez, Larissa Santana [UNESP]; Giro, Gabriela [UNESP]; Mendoza Marin, Danny Omar [UNESP]; Pero, Ana Carolina [UNESP] [UNESP] (Quintessence Publishing Co Inc, 2014)
The aim of this study was to assess the impact of replacing conventional mandibular complete dentures with implant-supported fixed complete dentures (ISFDs) on the oral health related quality of life (OHOOL) of edentulous patients and on the associated kinesiographic parameters. The patients had their complete dentures replaced by ISFDs and were assessed after 1, 2, 3, 6, and 12 months. An improvement of general OHQOL was observed 2 months after treatment with ISFDs. Kinesiographic recordings revealed significant mandibular vertical and horizontal opening increases and a greater vertical intrusion of the maxillary complete dentures during clenching after the treatment with ISFD.